Synergistic effects of heterostructure and pre-deformation on precipitation and corrosion behaviors of Al–Zn–Mg–Cu alloys - Jinming Zhi; Mingxing Guo; Tongbo Wang; Wen Meng; Wei Zhou; Linzhong Zhuang; Huafen Lou (Journal of Materials Research and Technology)
We report on a study of synergistic effects of heterostructure and pre-deformation on the precipitation and corrosion behaviors of Al–Zn–Mg–Cu alloys. Our results show that the constructed soft/hard micro-scale zone heterostructure enhances the strength i.e. yield strength from 428 to 486 MPa and corrosion resistance i.e. maximum intergranular corrosion depth from 55.8 to 46.4 μm of peak-aged alloys by applying an appropriate pre-deformation, whereas the elongation i.e. from 16.5% to 14% is negatively affected. The complex interactions that occur among the soft/hard micro-scale zones, intragranular/grain boundary precipitation, and homogeneous/heterogeneous nucleation lead to differences in precipitation and corrosion resistance for different microstructures. Our results provide fundamental insight into the precipitation and corrosion response in aged alloys with heterostructures, as a function of pre-deformation.